Effectiveness of E-module Based on Problem Research Based Learning (PRBL) on Students' Science Process Skills - Wuri Wardani; Baskoro Adi Prayitno; Lina Mahardiani (Postgraduate, University of Mataram, 2025)
The development of learning in the 21st century emphasizes the improvement of Science Process Skills (SPS). However, the implementation of SPS has not been able to be realized by teachers due to the limitations of the teaching materials used. The data obtained shows that the average value of SPS for students is still categorized as low, which is 43.3%. This study aims to test the effectiveness of the implementation of E-module based on Problem Research Based Learning (PRBL) on students' Science Process Skills (SPS). The research method used is Quasi Experimental research with research samples of class VIII A and VIII D in one of the Surakarta State Junior High Schools. The experimental class was given an e-module based on PRBL containing material on elements, compounds and mixtures while the control class used the BSE book with an interactive lecture method. The data collection technique used a written test instrument in the form of a SPS test with a reasoned multiple choice type. The effectiveness test used was the t-test, effect size and n-gain score. The results of the t-test showed a significance value of 0.00 which means there is a significant difference between the experimental class and the control class. These results prove that there is a difference in the results of students' SPS between the experimental class and the control class. Furthermore, the results of the effect size test with a moderate effect category of 0.63 and the n-gain score test with a high category of 0.702 for the experimental class. Based on the results of the three tests, it can be concluded that the implementation of PRBL-based e-modules is effective in increasing students' SPS.